Children's Perceptions of and Engagement in Urban Resilience in the United States and Mexico. (March 2019) - Derr, Victoria; Corona, Yolanda; Gülgönen, Tuline
Resilience planning is increasingly employed as a means for cities to anticipate and plan for environmental and social challenges. Children's perspectives are underrepresented in this domain. Through drawings, murals, photographs, videos, and dialogues, children shared their perspectives on resilience in two disparate cities—Boulder, Colorado, USA, and Mexico City, Mexico. Elements that support and negate resilience were consistent between cities. However, the negative aspects of physical and social safety were more acutely felt in Mexico City. While children were clear about what composes a resilient city, integration of these ideas into resilience planning was more challenging, especially in Mexico City.